Longitudinal follow-up of metformin treatment in Fragile X Syndrome - Seng, Panhaneath; Montanaro, Federica Alice Maria; Biag, Hazel Maridith Barlahan; Salcedo-Arellano, Maria Jimena; Kim, Kyoungmi; Ponzini, Matthew Dominic; Tassone, Flora; Schneider, Andrea; Abbeduto, Leonard; Thurman, Angela John; Hessl, David; Bolduc, Francois V.; et al. (Frontiers in Psychology, 2024)
Introduction: Metformin has been used as a targeted treatment to potentially improve cognition and slow the typical IQ decline that occurs during development among individuals with fragile X syndrome (FXS). In this follow-up study, we are following the trajectory of IQ and adaptive behavior changes over one to three years in individuals with FXS who are clinically treated with metformin in an open label trial. Method: Individuals with FXS ages 6 to 25 years (mean 13.15 ± 5.50) and nonverbal IQ mean 57.69 (±15.46) were treated for 1-3 years (1.88±0.63). They all had a baseline IQ test using the Leiter-III non-verbal cognitive assessment and the Vineland-III adaptive behavior assessment before the start of metformin. Repeat Leiter-III and Vineland-III were completed after at least one year of metformin (500mg – 1000mg/dose given twice a day). Result: There were no significant changes in non-verbal IQ or in the adaptive behavior measurements at FDR < 0.05. The findings thus far indicate that both IQ and adaptive behavior are stable over time, and we did not see a significant decline in either measure. Conclusion: Overall, the small sample size and short follow-up duration limit the interpretation of the effects of metformin on cognitive development and adaptive functioning. There is individual variability but overall for the group there was no significant decline in IQ or adaptive behavior.